MARKETING STRATEGY DEVELOPMENT OF GEOPARK CILETUH PELABUHAN RATU SUKABUMI - Besari, Anindita Putri; Hudrasyah, Herry (Journal of Business and Management, 2017)
Abstract. Background:Â Geopark Ciletuh Pelabuhan Ratu will be brought to an international UNESCO conference in which the achievement of Global Geopark will be determined. To be recognized as Global Geopark, there are several requirements to be fulfilled. However, the management is still hampered on the points of educational aspect, due to the number of visitors from the educational age is still on minimum rate. This research was conducted to understand the business environment of Geopark Ciletuh as a tourism destination and to develop marketing strategy for Geopark Ciletuh Pelabuhan Ratu with the aim of increasing the number of visitors. Methods:Â The research used qualitative approach by conducting in-depth interview with 2 person from the management of Geopark Ciletuh and 10 visitors of Geopark. Results:Â The research found that based on the results of environmental scanning, factors affecting Geopark Ciletuhâ??s business are considered potential to be developed and geopark tourism industry itself is in favorable condition. Analysis of visitorâ??s perception regarding the current condition of Geopark Ciletuh shows that further improvement regarding marketing mix is necessary. Conclusion: To reach the target market, marketing strategy is focused on the process of socialization, promotion and cooperation with several parties through intermediaries of social media and digital media by collaborating with local government and content creatorsÂ Keywords: ecotourism, Geopark, marketing mix, marketing strategy development, tourism industry